1995
DOI: 10.1007/bf00010486
|View full text |Cite
|
Sign up to set email alerts
|

Response of irrigated mulberry (Morus alba L.) to VA-mycorrhizal inoculation under graded doses of phosphorus

Abstract: A field experiment was conducted for four years with Kanva-2 variety of mulberry, pre-inoculated with Glomus fasciculatum and Glomus mosseae at various doses of single super phosphate to examine their effect on plant growth, leaf yield and quality. The pooled data for 4 years revealed that the effect of inoculation of mulberry with Glomus mosseae in combination with 30 kg P ha-l yr-I was similar for plant growth, leaf yield and leaf chemical constituents with the control, which received the full dose of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…These are known to occur globally in a broad range of dissimilar environments from artic to tropic and occupy a wide range of ecological niches [2]. The role of VAM fungi in the improvement of crop plant is well documented [3,4,5]. VAM fungi are known to improve the nutrient status of the plants, increase growth and development, protects plant against pathogen and confer resistance to drought and salinity [6].…”
Section: Introductionmentioning
confidence: 99%
“…These are known to occur globally in a broad range of dissimilar environments from artic to tropic and occupy a wide range of ecological niches [2]. The role of VAM fungi in the improvement of crop plant is well documented [3,4,5]. VAM fungi are known to improve the nutrient status of the plants, increase growth and development, protects plant against pathogen and confer resistance to drought and salinity [6].…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry plants, whose leaf is exclusively used for rearing silkworms (Bombyx mori L.) for subsequent cocoon production, have indicated their positive response towards the application of biofertilisers. The beneficial effect of inoculation of mulberry plants with Azotobacter bio-fertilizer and Vesicular Arbuscular mycorrhiza have been well documented by Das et al (1994a, b), Katiyar et al (1995) and Baqual et al (2005).…”
Section: Introductionmentioning
confidence: 82%
“…Thus, NP application can be curtailed to the tune of 25% by supplementing with bio-inoculants without adverse effect on fresh leaf yield of M 5 mulberry under rain-fed condition. Katiyar et al (1995) in their earlier studies on the effect of dual inoculation of A. chroococum and G. mosseae with 50% recommended dosage of N and P fertilizers have reported that, the yield of mulberry was on par with uninoculated control receiving full dosage of N and P fertilizers. Das et al (1994) in their studies have also reported that, there was no reduction in leaf yield in K 2 variety of mulberry when 50% nitrogen fertilizer was compensated with 20 kg Azotobacter sp./ha/year.…”
Section: Fresh Leaf Yield Per Plant (G/plant)mentioning
confidence: 97%
“…The lowest of the same were observed in T 8 (15.61 and 5.23 mg/g) (Tables 3 and 4). Katiyar et al (1995) and Umesh (1999) reported similar leaf chemical constituent in mulberry when biofertilizers were inoculated with reduced chemical fertilizers. Curtailment of 50% N application without affecting mulberry leaf quality by supplementing mulberry through 20 kg of Azotobacter has been reported by Das et al (1994).…”
Section: Crude Protein and Total Soluble Protein Content (Mg/g)mentioning
confidence: 97%